2005
DOI: 10.1118/1.1869612
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical tomography of breast cancer during neoadjuvant chemotherapy: A case study with comparison to MRI

Abstract: We employ diffuse optical tomography (DOT) to track treatment progress in a female subject presenting with locally advanced invasive carcinoma of the breast during neoadjuvant chemotherapy. Three-dimensional images of total hemoglobin concentration and scattering identified the tumor. Our measurements reveal tumor shrinkage during the course of chemotherapy, in reasonable agreement with magnetic resonance images of the same subject. A decrease in total hemoglobin concentration contrast between tumor and normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
226
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(232 citation statements)
references
References 71 publications
5
226
1
Order By: Relevance
“…This approach could be used to increase the sensitivity and/or specificity of the tomosynthesis exam depending upon the approach to use the prior information. Similarly, NIRS breast tumour imaging to quantify response from neoadjuvant chemotherapy with a posterior comparison to MRI by Choe et al [66] demonstrated that contrast reduction from NIRS added to the diagnostic value of MRI. Additionally, Jiang et al [67] examined the role of defining the region of interest based upon the size of the lesion in the initial pre-treatment image, and concluded that the quantitative estimate of tumour haemoglobin is significantly affected by the posterior estimate of lesion size.…”
Section: (C) Explicit Prior Shape Inclusion Applications and Analysismentioning
confidence: 99%
“…This approach could be used to increase the sensitivity and/or specificity of the tomosynthesis exam depending upon the approach to use the prior information. Similarly, NIRS breast tumour imaging to quantify response from neoadjuvant chemotherapy with a posterior comparison to MRI by Choe et al [66] demonstrated that contrast reduction from NIRS added to the diagnostic value of MRI. Additionally, Jiang et al [67] examined the role of defining the region of interest based upon the size of the lesion in the initial pre-treatment image, and concluded that the quantitative estimate of tumour haemoglobin is significantly affected by the posterior estimate of lesion size.…”
Section: (C) Explicit Prior Shape Inclusion Applications and Analysismentioning
confidence: 99%
“…Women with an increased genetic risk of DNA double-strand breaks when exposed to ionizing radiation might also benefit from optical imaging [105]. Optical mammography can be repeated as often as necessary without adverse effects, which is important, for example, to use the method for monitoring neoadjuvant chemotherapy [106,107]. Requiring little or no compression of the breast, optical imaging is more comfortable to the patient, which might improve compliance [108].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are handheld devices, which have been presented by several investigators and might increase specificity when combined with ultrasound. Another interesting use of intrinsic contrast imaging might be in monitoring patients undergoing neoadjuvant chemotherapy [106].…”
Section: Discussionmentioning
confidence: 99%
“…Recent pilot studies in both MRI and Near-Infrared Spectroscopy (NIR) have shown that more global estimates of cancer, such as water content and vascular volume changes, can be good predictors of response in primary breast cancer [14][15][16][17][18]. Total water content and vascular volume are robust signals in that they can be measured with a good signal to noise ratio, and biological variations in these are generally low, except in response to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Total water content and vascular volume are robust signals in that they can be measured with a good signal to noise ratio, and biological variations in these are generally low, except in response to intervention. Further, and of great potential interest, in pilot studies there is evidence that these biophysical changes occur within the first cycle of chemotherapy [14][15][16][17][18], which could have considerable prognostic value if confirmed with high specificity. Thus a key factor being tested in multi-center trials now is to determine the sensitivity and specificity of NIR or MRI as a measurement of response within the first cycle of NACT, and if this value is sufficient for a cost-effective test.…”
Section: Introductionmentioning
confidence: 99%